2017
DOI: 10.4317/jced.53877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of different surface treatments on the bond strength of different cements with nickel chromium metal alloy: An in vitro study

Abstract: BackgroundFor success of any indirect metal restoration, a strong bond between cement and the intaglio surface of metal is imperative. The aim of this study is to evaluate and compare the effect of different surface treatment on the tensile and shear bond strength of different cements with nickel–chromium alloy.Material and Methods120 premolars were sectioned horizontally parallel to the occlusal surface to expose the dentin. Wax patterns were fabricated for individual tooth followed by casting them in nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(23 reference statements)
2
3
0
Order By: Relevance
“…However, P&B NT pretreatment had no statistical significance, maybe the physical property is more important in the bonding mechanism for RelyX Luting. Kapoor et al () and Piwowarczyk, Lauer and Sorensen () has reported that RMGIC provided lower bond strength values than self‐adhesive resin cement, which was also found in this study. Berzins, Abey, Costache, Wilkie, and Roberts () demonstrated that during early RMGIC development, acid‐base and light‐polymerization reactions competed with and inhibited one another, which might explain the low retentive strength of RMGIC.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, P&B NT pretreatment had no statistical significance, maybe the physical property is more important in the bonding mechanism for RelyX Luting. Kapoor et al () and Piwowarczyk, Lauer and Sorensen () has reported that RMGIC provided lower bond strength values than self‐adhesive resin cement, which was also found in this study. Berzins, Abey, Costache, Wilkie, and Roberts () demonstrated that during early RMGIC development, acid‐base and light‐polymerization reactions competed with and inhibited one another, which might explain the low retentive strength of RMGIC.…”
Section: Discussionsupporting
confidence: 87%
“…However, P&B NT pretreatment had no statistical significance, maybe the physical property is more important in the bonding mechanism for RelyX Luting. Kapoor et al (2017) and Piwowarczyk, Lauer and Sorensen (2004) has reported that RMGIC provided lower bond strength values than self-adhesive resin cement, which was also found in this study. Berzins, Abey, Costache, Wilkie, and Roberts (2010) Thermocycling has been widely used to simulate thermal stresses commonly occurring in the oral environment and has been performed to compare bond strength according to aging (Lee, Kang, Oh, Seo, & Park, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… Conditioning of zirconia‐based laminate veneers: through sandblasting for 10 s at 0.2 MPa pressure using 50 μm diameter Al 2 O 3 particles, then ultrasonic cleaning for 5 min and dried, then primer left for 60 s and air dried for 5 s (Monobond plus primer Ivoclar Vivadent) (Gresnigt et al, 2021 ; Saker & Özcan, 2021 ). Conditioning of the corresponding metal dies surfaces: done by oxidation, sandblasting for 20 s at 0.3 MPa pressure using 150 μm diameter Al 2 O 3 particles, ultrasonic clean for 5 min, air dried and finally primer applicated for 60 s and air dried for 5 s (Kapoor et al, 2017 ). …”
Section: Methodsmentioning
confidence: 99%
“…Conditioning of the corresponding metal dies surfaces: done by oxidation, sandblasting for 20 s at 0.3 MPa pressure using 150 μm diameter Al 2 O 3 particles, ultrasonic clean for 5 min, air dried and finally primer applicated for 60 s and air dried for 5 s (Kapoor et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%